A SCR denitration catalyst hardening liquid and its preparation method and application
By using a hardening liquid composed of aluminum hydroxide, phosphoric acid, silica sol, Cu-Fe-Ce molecular sieve and polyvinyl alcohol, the problem of insufficient wear resistance and denitrification activity in SCR denitrification catalyst hardening technology is solved, and the catalyst hardening end is realized Highly efficient denitrification and long life.
Patent Information
- Application Number
- CN202110274101.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-12
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-03-12
AI Technical Summary
The existing SCR denitrification catalyst hardening technology has problems with insufficient wear resistance and denitrification activity, which leads to shortening the service life of the catalyst and unstable device.
Using a hardening liquid composed of aluminum hydroxide, phosphoric acid, silicon sol, Cu-Fe-Ce molecular sieve and polyvinyl alcohol, a hardener with high adhesion and wear resistance is formed through specific preparation methods and treatment steps to improve the catalyst. Denitrification activity and wear resistance at the hardened end.
It significantly improves the denitrification performance and wear resistance of the hardened end of the catalyst, extends the service life of the catalyst, and ensures the stable operation of the device.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of SCR denitration catalysts, and in particular to a SCR denitration catalyst hardening liquid and a preparation method and application thereof. Background Art
[0002] NOx is one of the main pollutants in the atmospheric environment. It not only causes environmental problems such as haze, acid rain, and photochemical smog, but also has adverse effects on human health. With the improvement of national environmental protection policies, NOx emission control is becoming increasingly strict. At present, among the many flue gas denitrification technologies, the selective catalytic reduction (SCR) technology using NH3 as a reducing agent is the most mature and widely used, with the core being the denitrification catalyst. The most industrially used is the vanadium-tungsten-titanium SCR denitrification catalyst, among which the honeycomb catalyst has a large market share.
[0003] During the use of catalysts, they are often washed by dust in the flue gas, and the top of the catalyst is easily worn, which may cause problems such as catalyst breakage, collapse, and pore blockage, shortening the service life of the catalyst. In severe cases, it may cause abnormal shutdown of the denitration device. For this reason, the top of the catalyst is hardened in the industrial production of catalysts, but there are still some problems with the existing hardening technology, such as poor wear resistance of the hardened end of the catalyst and basically no denitration activity at the hardened end of the catalyst.
[0004] Patent application number CN201711347208.0 discloses a process for hardening the windward end of an SCR denitration catalyst, in which a calcined SCR denitration catalyst is vertically inserted into a prepared impregnation liquid, and then the impregnated catalyst is dried in a hot air furnace to complete the hardening. Although this hardening process can improve the catalyst's anti-wear performance and extend the catalyst's service life, the hardened portion of the catalyst port has no denitration activity.
[0005] The patent with application number CN201511015705.1 discloses a catalyst end face hardening hydrosol and a preparation method. The SCR denitration catalyst end face hardening hydrosol includes an aluminum sulfate solution with a concentration of 20% to 27%, an oxalic acid solution with a concentration of 25% to 50%, and an ammonium metavanadate solution with a concentration of 33% to 66%; wherein the weight ratio of the oxalic acid solution to the ammonium metavanadate solution is (0.6 to 1): 1, and the oxalic acid solution and the ammonium metavanadate solution are mixed to form a mixed solution; the weight ratio of the aluminum sulfate solution, the mixed solution and polyvinyl alcohol is 1: (0.1 to 0.2): 0.02. The hardening liquid formula of the patent uses an aluminum sulfate solution, and the amount of aluminum hydroxide that can be generated by the hydrolysis of aluminum sulfate is relatively limited, so that the adsorption force of the anti-wear substance in the SCR denitration catalyst is relatively limited.
[0006] Patent application number CN201410202244.8 discloses a method for hardening the end of an SCR denitration catalyst. The method comprises the following specific steps: (1) preparing an active solution: weighing 1 to 5 parts of ammonium metatungstate, 0.5 to 1 part of cerium nitrate, and 1 to 2 parts of ammonium heptamolybdate, respectively, and dissolving them in 100 parts of deionized water; (2) weighing 20 to 35 parts of ammonium dihydrogen phosphate, and dissolving them in 100 parts of deionized water; (3) mixing the two solutions of step (1) and step (2), heating them to 80°C, and stirring them evenly; (4) dipping one or both ends of the honeycomb catalyst module to be hardened in the solution of step (3) for 5s to 10s; (5) taking out the impregnated catalyst from step (4) and placing it in a muffle furnace and calcining it at 110°C for 30min, so that the components therein react with the catalyst to ensure that the edges of one or both ends of the catalyst are hardened. The patent introduces active components into the hardening liquid, which can make the hardened part of the catalyst have denitrification activity and improve the end hardness to a certain extent. Especially in the use range of 300-420℃, it is difficult to form an obvious protective film on the hardened part of the catalyst, and the anti-wear performance needs to be improved.
[0007] Patents with application numbers CN201310243987.5 and CN201310244764.0 respectively disclose a hardening liquid formula and hardening process for an SCR denitration catalyst module. The formula of the hardening liquid includes the following components, specifically 2-5% aluminum hydroxide, 6-20% phosphoric acid, 1-5% vanadium pentoxide as an active component, and the balance is water. The hardening process is as follows: (1) prepare the hardening liquid according to the above hardening liquid composition; (2) immerse both ends or one end of the catalyst that has been formed and dried or sintered in the hardening liquid for 10-30 seconds, take it out and air dry it, the air temperature of the air drying is 10-20°C, and the air humidity is 30-50%; (3) the impregnated catalyst is calcined at a temperature of 190-420°C. The hardening liquid formula and hardening process of the above patents can improve the wear resistance and denitration activity of the catalyst and extend the service life of the catalyst. However, aluminum dihydrogen phosphate in the hardening liquid is a thermosetting material. It will decompose and dehydrate when heated. Generally, it will shrink greatly, the bonding layer will deform, and the bonding force will be reduced to varying degrees. Therefore, it is necessary to improve the bonding force and strength of the main component of the hardening liquid to meet the requirements of different operating temperatures of the catalyst.
[0008] Therefore, the present invention is committed to developing a hardening liquid and a preparation method thereof with simple process, good anti-wear performance and good denitrification activity at the hardening end, so as to extend the service life of the catalyst and ensure the stable operation of the device for a longer period of time. Summary of the invention
[0009] The object of the present invention is to provide a SCR denitration catalyst hardening liquid and a preparation method and application thereof, wherein the SCR denitration catalyst hardening liquid can improve the denitration performance and anti-wear performance of the hardened end of the catalyst, and effectively ensure the normal service life of the catalyst.
[0010] To achieve the above-mentioned purpose, the present invention provides an SCR denitration catalyst hardening liquid, which includes the following component raw materials in weight ratio: 20% to 55% deionized water, 4% to 22% aluminum hydroxide, 15% to 65% phosphoric acid, 1% to 20% silica sol, 2% to 25% Cu-Fe-Ce molecular sieve, and 0.05% to 2% polyvinyl alcohol.
[0011] The Cu-Fe-Ce molecular sieve described in the present invention is any one of ZSM-5, β molecular sieve, USY, SSZ-13 and SAPO-34 or a mixture of several of them.
[0012] Furthermore, the hardening solution includes the following raw materials in weight ratio: 25% to 50% water, 8% to 20% aluminum hydroxide, 25% to 60% phosphoric acid, 2% to 15% silica sol, 5% to 15% Cu-Fe-Ce molecular sieve, and 0.1% to 1.5% polyvinyl alcohol.
[0013] The present invention also provides a method for preparing a hardening liquid for an SCR denitration catalyst, using the above-mentioned hardening liquid raw material formula, and the preparation method comprises the following steps:
[0014] Step (1): dissolving phosphoric acid in water to form a phosphoric acid solution;
[0015] Step (2): adding aluminum hydroxide to the phosphoric acid solution to prepare an aluminum dihydrogen phosphate solution;
[0016] Step (3): adding silica sol to the aluminum dihydrogen phosphate solution to form an aluminum dihydrogen phosphate-silica sol mixed solution;
[0017] Step (4): adding Cu-Fe-Ce molecular sieve to the mixed solution of step (3) and mixing evenly;
[0018] Step (5): Add polyvinyl alcohol to the solution of step (4) to obtain a SCR denitration catalyst hardening liquid.
[0019] Wherein, in the above step (1), the phosphoric acid is dissolved in deionized water, stirred at a constant speed, and heated to 70-80° C. to form a phosphoric acid solution.
[0020] In the above step (2), aluminum hydroxide is added to the phosphoric acid solution, stirred at a constant speed, and heated to 90-95° C. to obtain an aluminum dihydrogen phosphate solution.
[0021] In the above step (3), the silica sol is added to the aluminum dihydrogen phosphate solution, stirred at a uniform speed, and heated to 85-95° C. to form an aluminum dihydrogen phosphate-silica sol mixed solution.
[0022] The present invention further provides a method for using an SCR denitration catalyst hardening liquid in the hardening treatment of an SCR denitration catalyst. The method comprises: vertically inserting a pre-hardened end of the SCR denitration catalyst into the above-mentioned SCR denitration catalyst hardening liquid for immersion for 5 to 35 seconds. After the immersion is completed, air-drying at room temperature for 10 to 24 hours to obtain a hardened SCR denitration catalyst.
[0023] The SCR denitration catalyst hardening liquid provided by the present invention is prepared in proportion by aluminum hydroxide, phosphoric acid, silica sol, Cu-Fe-Ce molecular sieve, polyvinyl alcohol, etc., and has strong bonding force and good wear resistance. The bonding performance of the SCR denitration catalyst hardening liquid of the present invention is mainly achieved through the inorganic polymer skeleton. The spatial structure of phosphoric acid is a phosphorus oxygen tetrahedron. During the heating process, POP reacts with POP to dehydrate and polymerize through oxygen bridging to form tetraphosphoric acid; and in the process of reaction with silicon and aluminum, a cyclic inorganic polymer structure with covalent bonds and ionic bonds as the skeleton structure can be formed to enhance the bonding ability. In addition, silica sol, as a highly active adsorption material, has adsorption and complexation effects on aluminum, and can also improve the strength of the adhesive, thereby promoting better combination of various raw materials. The SCR denitration catalyst curing liquid of the present invention introduces Cu-Fe-Ce molecular sieves. Since the Cu-Fe-Ce molecular sieves have the characteristics of high strength and strong anti-scouring performance, and have a uniform microporous structure and excellent adsorption performance, this is more conducive to the catalytic reduction reaction of NOx in the flue gas in the pores, and has excellent denitration performance. The introduction of Cu-Fe-Ce molecular sieves in the SCR denitration catalyst curing liquid can keep the catalyst hardened end active to a certain extent. At the same time, polyvinyl alcohol can promote the uniform dispersion and non-sedimentation of the components in the curing liquid, and can condense on the surface of the catalyst to form a protective film. The interaction of aluminum hydroxide, phosphoric acid, silica sol, Cu-Fe-Ce molecular sieves and polyvinyl alcohol is more conducive to improving the port hardening ability of the curing liquid. In addition, the SCR denitration catalyst curing liquid prepared by the present invention can improve the denitration activity and wear resistance of the catalyst and extend the service life of the catalyst. DETAILED DESCRIPTION
[0024] The following is a detailed description of the embodiments of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and process are given, but the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0025] The invention provides a method for preparing a SCR denitration catalyst hardening liquid. The SCR denitration catalyst hardening liquid is composed of deionized water, aluminum hydroxide, phosphoric acid, silica sol, Cu-Fe-Ce molecular sieve and polyvinyl alcohol and is prepared in a certain proportion.
[0026] The present invention also provides an application of an SCR denitration catalyst hardening liquid in hardening treatment of an SCR denitration catalyst. The method of use comprises vertically inserting a pre-hardened end of the catalyst into the SCR denitration catalyst hardening liquid for immersion, the immersion time being 5 to 35 seconds. After the immersion is completed, air-drying at room temperature for 10 to 24 hours to obtain a hardened SCR denitration catalyst.
[0027] The wear performance of the catalyst of the present invention is tested according to the standard "Honeycomb Flue Gas Denitration Catalyst" GB / T31587-2015.
[0028] Evaluation conditions for the denitration performance of the catalyst of the present invention: space velocity 7000h -1 , reaction temperature 350℃, intake NOx 400mg / Nm 3 , O2 content is 3.0%, H2O content is 10%, and ammonia nitrogen ratio is 1.
[0029] Catalyst specifications: 30×30×200mm (taken from industrial samples)
[0030] The wear rate of the catalyst without hardening treatment was 0.12% / kg.
[0031] Sources of raw materials for preparing the hardening solution in the embodiment of the present invention:
[0032] Phosphoric acid: Sinopharm Chemical Reagent Co., Ltd.
[0033] Aluminum hydroxide: Sinopharm Chemical Reagent Co., Ltd.
[0034] Silica sol: Sinopharm Chemical Reagent Co., Ltd.
[0035] Cu-Fe-Ce molecular sieve: homemade
[0036] Polyvinyl alcohol: Sinopharm Chemical Reagent Co., Ltd.
[0037] Embodiment 1:
[0038] 65 g of phosphoric acid was weighed and dissolved in 80 g of deionized water to obtain a phosphoric acid solution, which was stirred at a uniform speed and heated to 70° C.; then 30 g of aluminum hydroxide was slowly added to the phosphoric acid solution to obtain an aluminum dihydrogen phosphate solution, which was stirred at a uniform speed and heated to 90° C.; 5 g of silica sol was added to the aluminum dihydrogen phosphate solution to obtain an aluminum dihydrogen phosphate-silica sol mixed solution, which was stirred at a uniform speed and heated to 90° C.; 15 g of Cu-Fe-Ce / ZSM-5 was added to the aluminum dihydrogen phosphate-silica sol mixed solution, wherein Cu was 0.5 wt%, Fe was 1.0 wt%, and Ce was 0.2 wt%, and the mixture was stirred at a uniform speed to obtain an aluminum dihydrogen phosphate-silica sol-Cu-Fe-Ce / ZSM-5 mixed solution; finally, 0.7 g of polyvinyl alcohol was added to the above mixed solution, and the mixture was stirred at a uniform speed to obtain a hardening solution.
[0039] The pre-hardened end of the denitrification catalyst with a specification of 30×30×200mm was vertically inserted into the hardening liquid for immersion. The immersion liquid depth was 5mm and the immersion time was 20s. After the immersion was completed, it was air-dried at room temperature for 20h and then the anti-wear performance was evaluated. The results showed that the catalyst wear rate was 0.07% / kg.
[0040] All denitration catalysts with specifications of 30×30×200mm were vertically inserted into the hardening liquid for immersion for 20s. After immersion, they were air-dried at room temperature for 20h and then the denitration performance was evaluated. The results showed that the denitration efficiency of the catalyst was about 51.5%.
[0041] Comparative Example 1:
[0042] Weigh 65g of phosphoric acid and dissolve it in 80g of deionized water to obtain a phosphoric acid solution. During this process, stir at a uniform speed and heat to 70°C. Then slowly add 30g of aluminum hydroxide to the phosphoric acid solution to obtain a dihydrogen aluminum phosphate solution. During this process, stir at a uniform speed and heat to 90°C. Then add 5g of silica sol to the dihydrogen aluminum phosphate solution to obtain a dihydrogen aluminum phosphate-silica sol mixed solution. During this process, stir at a uniform speed and heat to 90°C. Finally, add 0.7g of polyvinyl alcohol to the above mixed solution and stir at a uniform speed to obtain a hardening solution.
[0043] Compared with Example 1, no Cu-Fe-Ce molecular sieve is added in the preparation step of the catalyst.
[0044] The pre-hardened end of the denitrification catalyst with a specification of 30×30×200mm was vertically inserted into the hardening liquid for immersion. The immersion liquid depth was 5mm and the immersion time was 20s. After the immersion was completed, it was air-dried at room temperature for 20h and then the anti-wear performance was evaluated. The results showed that the catalyst wear rate was 0.09% / kg.
[0045] All denitrification catalysts with specifications of 30×30×200mm were vertically inserted into the hardening liquid and immersed for 20s. After the immersion was completed, they were air-dried at room temperature for 20h and then the denitrification performance was evaluated. The results showed that the catalyst had basically no denitrification effect.
[0046] Embodiment 2:
[0047] 100g of phosphoric acid was weighed and dissolved in 100g of deionized water to obtain a phosphoric acid solution. During this process, it was stirred at a uniform speed and heated to 75°C. Then, 25g of aluminum hydroxide was slowly added to the phosphoric acid solution to obtain a dihydrogen aluminum phosphate solution. During this process, it was stirred at a uniform speed and heated to 90°C. Then, 10g of silica sol was added to the dihydrogen aluminum phosphate solution to obtain a dihydrogen aluminum phosphate-silica sol mixed solution. During this process, it was stirred at a uniform speed and heated to 95°C. 25g of Cu-Fe-Ce / β was continuously added to the dihydrogen aluminum phosphate-silica sol mixed solution, wherein Cu was 1.5wt%, Fe was 2.5wt%, and Ce was 0.5wt%, and it was stirred at a uniform speed to obtain a dihydrogen aluminum phosphate-silica sol-Cu-Fe-Ce / β mixed solution. Finally, 1g of polyvinyl alcohol was added to the above mixed solution, and it was stirred at a uniform speed to obtain a hardening liquid.
[0048] The pre-hardened end of the denitrification catalyst with a specification of 30×30×200mm was vertically inserted into the hardening liquid for immersion. The immersion liquid depth was 5mm and the immersion time was 20s. After the immersion was completed, it was air-dried at room temperature for 24h and then the anti-wear performance was evaluated. The results showed that the catalyst wear rate was 0.06% / kg.
[0049] All denitrification catalysts with specifications of 30×30×200mm were vertically inserted into the hardening liquid for immersion for 20s. After immersion, they were air-dried at room temperature for 24h and then the denitrification performance was evaluated. The results showed that the denitrification efficiency of the catalyst was about 54.6%.
[0050] Comparative Example 2:
[0051] Weigh 100g of phosphoric acid and dissolve it in 100g of deionized water to obtain a phosphoric acid solution. During this process, stir at a uniform speed and heat to 75°C. Then slowly add 25g of aluminum hydroxide to the phosphoric acid solution to obtain a dihydrogen aluminum phosphate solution. During this process, stir at a uniform speed and heat to 90°C. Then add 10g of silica sol to the dihydrogen aluminum phosphate solution to obtain a dihydrogen aluminum phosphate-silica sol mixed solution. During this process, stir at a uniform speed and heat to 95°C. Finally, add 1g of polyvinyl alcohol to the above mixed solution and stir at a uniform speed to obtain a hardening solution.
[0052] Compared with Example 2, no Cu-Fe-Ce molecular sieve is added in the preparation step of the catalyst.
[0053] The pre-hardened end of the denitrification catalyst with a specification of 30×30×200mm was vertically inserted into the hardening liquid for immersion. The immersion liquid depth was 5mm and the immersion time was 20s. After the immersion was completed, it was air-dried at room temperature for 24h and then the anti-wear performance was evaluated. The results showed that the catalyst wear rate was 0.08% / kg.
[0054] All denitrification catalysts with specifications of 30×30×200mm were vertically inserted into the hardening liquid and immersed for 20s. After the immersion was completed, they were air-dried at room temperature for 24h and then the denitrification performance was evaluated. The results showed that the catalyst had basically no denitrification effect.
[0055] Embodiment 3:
[0056] 75 g of phosphoric acid was weighed and dissolved in 100 g of deionized water to obtain a phosphoric acid solution, which was stirred at a uniform speed and heated to 80° C. Then 20 g of aluminum hydroxide was slowly added to the phosphoric acid solution to obtain an aluminum dihydrogen phosphate solution, which was stirred at a uniform speed and heated to 95° C. Then 12 g of silica sol was added to the aluminum dihydrogen phosphate solution to obtain an aluminum dihydrogen phosphate-silica sol mixed solution, which was stirred at a uniform speed and heated to 95° C. 20 g of Cu-Fe-Ce / ZSM-5 was added to the aluminum dihydrogen phosphate-silica sol mixed solution, wherein Cu was 1.5 wt%, Fe was 3.0 wt%, and Ce was 0.8 wt%, and the mixture was stirred at a uniform speed to obtain an aluminum dihydrogen phosphate-silica sol-Cu-Fe-Ce / ZSM-5 mixed solution; finally, 1.2 g of polyvinyl alcohol was added to the above mixed solution, and the mixture was stirred at a uniform speed to obtain a hardening solution.
[0057] The pre-hardened end of the denitrification catalyst with a specification of 30×30×200mm was vertically inserted into the hardening liquid for immersion. The immersion liquid depth was 5mm and the immersion time was 25s. After the immersion was completed, it was air-dried at room temperature for 15h and then the anti-wear performance was evaluated. The results showed that the catalyst wear rate was 0.05% / kg.
[0058] All denitrification catalysts with specifications of 30×30×200mm were vertically inserted into the hardening liquid for immersion for 25s. After the immersion was completed, they were air-dried at room temperature for 15h and then the denitrification performance was evaluated. The results showed that the denitrification efficiency of the catalyst was about 55.3%.
[0059] Comparative Example 3:
[0060] 75 g of phosphoric acid was weighed and dissolved in 100 g of deionized water to obtain a phosphoric acid solution. During this process, the solution was stirred at a uniform speed and heated to 80° C. Then, 20 g of aluminum hydroxide was slowly added to the phosphoric acid solution to obtain a dihydrogen aluminum phosphate solution. During this process, the solution was stirred at a uniform speed and heated to 95° C. Then, 20 g of Cu-Fe-Ce / ZSM-5, wherein Cu was 1.5 wt%, Fe was 3.0 wt%, and Ce was 0.8 wt%, was added to the dihydrogen aluminum phosphate solution, and the solution was stirred at a uniform speed to obtain a dihydrogen aluminum phosphate-Cu-Fe-Ce / ZSM-5 mixed solution. Finally, 1.2 g of polyvinyl alcohol was added to the mixed solution, and the solution was stirred at a uniform speed to obtain a hardening solution.
[0061] Compared with Example 3, no silica sol is added in the preparation step of the catalyst.
[0062] The pre-hardened end of the denitrification catalyst with a specification of 30×30×200mm was vertically inserted into the hardening liquid for immersion. The immersion liquid depth was 5mm and the immersion time was 25s. After the immersion was completed, it was air-dried at room temperature for 15h and then the anti-wear performance was evaluated. The results showed that the catalyst wear rate was 0.07% / kg.
[0063] All denitrification catalysts with specifications of 30×30×200mm were vertically inserted into the hardening liquid for immersion for 25s. After immersion, they were air-dried at room temperature for 15h and then the denitrification performance was evaluated. The results showed that the denitrification efficiency of the catalyst was about 55.9%.
[0064] Embodiment 4:
[0065] 110 g of phosphoric acid was weighed and dissolved in 90 g of deionized water to obtain a phosphoric acid solution, which was stirred at a uniform speed and heated to 75° C.; then 20 g of aluminum hydroxide was slowly added to the phosphoric acid solution to obtain an aluminum dihydrogen phosphate solution, which was stirred at a uniform speed and heated to 95° C.; 15 g of silica sol was added to the aluminum dihydrogen phosphate solution to obtain an aluminum dihydrogen phosphate-silica sol mixed solution, which was stirred at a uniform speed and heated to 90° C.; 25 g of Cu-Fe-Ce / ZSM-5 was added to the aluminum dihydrogen phosphate-silica sol mixed solution, wherein Cu was 2.5 wt%, Fe was 4.0 wt%, and Ce was 1.0 wt%, and the mixture was stirred at a uniform speed to obtain an aluminum dihydrogen phosphate-silica sol-Cu-Fe-Ce / ZSM-5 mixed solution; finally, 1.5 g of polyvinyl alcohol was added to the above mixed solution, and the mixture was stirred at a uniform speed to obtain a hardening solution.
[0066] The pre-hardened end of the denitrification catalyst with a specification of 30×30×200mm was vertically inserted into the hardening liquid for immersion. The immersion liquid depth was 5mm and the immersion time was 30s. After the immersion was completed, it was air-dried at room temperature for 20h and then the anti-wear performance was evaluated. The results showed that the catalyst wear rate was 0.04% / kg.
[0067] All denitration catalysts with specifications of 30×30×200mm were vertically inserted into the hardening liquid for 30s. After the immersion, they were air-dried at room temperature for 20h and then the denitration performance was evaluated. The results showed that the denitration efficiency of the catalyst was about 59.8%.
[0068] Comparative Example 4:
[0069] Weigh 110g of phosphoric acid and dissolve it in 90g of deionized water to obtain a phosphoric acid solution. During this process, stir at a uniform speed and heat to 75°C. Then slowly add 20g of aluminum hydroxide to the phosphoric acid solution to obtain a dihydrogen aluminum phosphate solution. During this process, stir at a uniform speed and heat to 95°C. Then add 1.5g of polyvinyl alcohol to the dihydrogen aluminum phosphate solution and stir at a uniform speed to obtain a hardening solution.
[0070] Compared with Example 4, no silica sol and Cu-Fe-Ce molecular sieve were added in the preparation step of the catalyst.
[0071] The pre-hardened end of the denitrification catalyst with a specification of 30×30×200mm was vertically inserted into the hardening liquid for immersion. The immersion liquid depth was 5mm and the immersion time was 30s. After the immersion was completed, it was air-dried at room temperature for 20h and then the anti-wear performance was evaluated. The results showed that the catalyst wear rate was 0.09% / kg.
[0072] All denitrification catalysts with specifications of 30×30×200mm were vertically inserted into the hardening liquid and immersed for 30s. After the immersion was completed, they were air-dried at room temperature for 20h and then the denitrification performance was evaluated. The results showed that the catalyst had basically no denitrification effect.
[0073] Embodiment 5:
[0074] 55 g of phosphoric acid was weighed and dissolved in 70 g of deionized water to obtain a phosphoric acid solution. During the process, the solution was stirred at a uniform speed and heated to 80° C. Then, 40 g of aluminum hydroxide was slowly added to the phosphoric acid solution to obtain an aluminum dihydrogen phosphate solution. During the process, the solution was stirred at a uniform speed and heated to 90° C. Then, 15 g of silica sol was added to the aluminum dihydrogen phosphate solution to obtain an aluminum dihydrogen phosphate-silica sol mixed solution. During the process, the solution was stirred at a uniform speed and heated to 85° C. 20 g of Cu-Fe-Ce / ZSM-5 was added to the aluminum dihydrogen phosphate-silica sol mixed solution, wherein Cu was 2.0 wt%, Fe was 4.0 wt%, and Ce was 1.0 wt%, and the mixture was stirred at a uniform speed to obtain an aluminum dihydrogen phosphate-silica sol-Cu-Fe-Ce / ZSM-5 mixed solution. Finally, 2 g of polyvinyl alcohol was added to the above mixed solution and stirred at a uniform speed to obtain a hardening solution.
[0075] The pre-hardened end of the denitrification catalyst with a specification of 30×30×200mm was vertically inserted into the hardening liquid for immersion. The immersion liquid depth was 5mm and the immersion time was 30s. After the immersion was completed, it was air-dried at room temperature for 24h and then the anti-wear performance was evaluated. The results showed that the catalyst wear rate was 0.06% / kg.
[0076] All denitration catalysts with specifications of 30×30×200mm were vertically inserted into the hardening liquid for immersion for 30s. After immersion, they were air-dried at room temperature for 24h and then the denitration performance was evaluated. The results showed that the denitration efficiency of the catalyst was about 56.4%.
[0077] Comparative Example 5:
[0078] 55 g of phosphoric acid was weighed and dissolved in 70 g of deionized water to obtain a phosphoric acid solution. During this process, the solution was stirred at a uniform speed and heated to 80° C. Then, 40 g of aluminum hydroxide was slowly added to the phosphoric acid solution to obtain a dihydrogen aluminum phosphate solution. During this process, the solution was stirred at a uniform speed and heated to 90° C. Then, 20 g of Cu-Fe-Ce / ZSM-5, wherein Cu 2.0 wt%, Fe 4.0 wt%, and Ce 1.0 wt%, was added to the dihydrogen aluminum phosphate solution and stirred at a uniform speed to obtain a dihydrogen aluminum phosphate-Cu-Fe-Ce / ZSM-5 mixed solution. Finally, 2 g of polyvinyl alcohol was added to the mixed solution and stirred at a uniform speed to obtain a hardening solution.
[0079] Compared with Example 5, no silica sol is added in the preparation step of the catalyst.
[0080] The pre-hardened end of the denitrification catalyst with a specification of 30×30×200mm was vertically inserted into the hardening liquid for immersion. The immersion liquid depth was 5mm and the immersion time was 30s. After the immersion was completed, it was air-dried at room temperature for 24h and then the anti-wear performance was evaluated. The results showed that the catalyst wear rate was 0.07% / kg.
[0081] All denitration catalysts with specifications of 30×30×200mm were vertically inserted into the hardening liquid for immersion for 30s. After immersion, they were air-dried at room temperature for 24h and then the denitration performance was evaluated. The results showed that the denitration efficiency of the catalyst was about 56.0%.
[0082] Through the examples and comparative examples, it is found that silica sol and Cu-Fe-Ce molecular sieve will cause changes in anti-wear performance or denitration performance to varying degrees, and the interaction of the components of the hardening liquid jointly promotes the change in performance. Compared with the comparative example, the catalyst treated with the SCR denitration catalyst hardening liquid of the present invention has better denitration performance and anti-wear performance.
[0083] In summary, the hardening liquid prepared in proportion by aluminum hydroxide, phosphoric acid, silica sol, Cu-Fe-Ce molecular sieve, polyvinyl alcohol, etc. can not only improve the wear resistance of the hardened end surface of the catalyst, but also improve the denitrification activity of the hardened end of the catalyst.
[0084] The present invention is not limited to the aforementioned specific embodiments, and any changes or modifications made by any technician in the field of the present invention are all covered by the patent scope of the present invention.
Claims
1. A SCR denitration catalyst curing liquid, characterized in that: The raw materials include the following components in weight ratio: 20-55% deionized water, 4-22% aluminum hydroxide, 15-65% phosphoric acid, 1-20% silica sol, 2-25% Cu-Fe-Ce molecular sieve, and 0.05-2% polyvinyl alcohol; The molecular sieve in the Cu-Fe-Ce molecular sieve is any one or a mixture of several of ZSM-5, β molecular sieve, USY, SSZ-13, and SAPO-34; The method for preparing the SCR denitration catalyst hardening liquid comprises the following steps: Step (1): dissolving phosphoric acid in deionized water to form a phosphoric acid solution; Step (2): adding aluminum hydroxide to the phosphoric acid solution to prepare an aluminum dihydrogen phosphate solution; Step (3): adding silica sol to the aluminum dihydrogen phosphate solution to form an aluminum dihydrogen phosphate-silica sol mixed solution; Step (4): adding Cu-Fe-Ce molecular sieve to the mixed solution of step (3) and mixing evenly; Step (5): Add polyvinyl alcohol to the solution obtained in step (4) to obtain a SCR denitration catalyst hardening solution.
2. The SCR denitration catalyst curing liquid according to claim 1, characterized in that: The raw materials include the following components in weight ratio: 20% to 50% deionized water, 8% to 20% aluminum hydroxide, 25% to 60% phosphoric acid, 2% to 15% silica sol, 5% to 15% Cu-Fe-Ce molecular sieve, and 0.1% to 1.5% polyvinyl alcohol.
3. A method for preparing a SCR denitration catalyst hardening liquid according to any one of claims 1 to 2, characterized in that: The following steps are involved: Step (1): dissolving phosphoric acid in deionized water to form a phosphoric acid solution; Step (2): adding aluminum hydroxide to the phosphoric acid solution to prepare an aluminum dihydrogen phosphate solution; Step (3): adding silica sol to the aluminum dihydrogen phosphate solution to form an aluminum dihydrogen phosphate-silica sol mixed solution; Step (4): adding Cu-Fe-Ce molecular sieve to the mixed solution of step (3) and mixing evenly; Step (5): Add polyvinyl alcohol to the solution obtained in step (4) to obtain a SCR denitration catalyst hardening solution.
4. The method for preparing the SCR denitration catalyst curing liquid according to claim 3, characterized in that: In step (1), the phosphoric acid is dissolved in deionized water, stirred at a constant speed, and heated to 70-80° C. to form a phosphoric acid solution.
5. The method for preparing the SCR denitration catalyst hardening liquid according to claim 3, characterized in that: In step (2), aluminum hydroxide is added to the phosphoric acid solution, stirred at a uniform speed, and heated to 90-95° C. to obtain an aluminum dihydrogen phosphate solution.
6. The method for preparing the SCR denitration catalyst curing liquid according to claim 3, characterized in that: In step (3), the silica sol is added to the aluminum dihydrogen phosphate solution, stirred at a uniform speed, and heated to 85-95° C. to form an aluminum dihydrogen phosphate-silica sol mixed solution.
7. Use of the SCR denitration catalyst hardening liquid according to any one of claims 1 to 2 in hardening treatment of SCR denitration catalyst, characterized in that: include: The pre-hardened end of the SCR denitration catalyst is vertically inserted into the SCR denitration catalyst hardening liquid according to any one of claims 1-2 for immersion, and the immersion time is 5-35 seconds. After the immersion is completed, it is air-dried at room temperature for 10-24 hours to obtain a hardened SCR denitration catalyst.